A Systematic Review in Digital Entrepreneurship Ecosystems - Giotopoulos, Konstantinos (Technium Social Sciences Journal, 2024)
This study conducts a systematic review of Digital Entrepreneurship Ecosystems (DEEs), focusing on their organization, development, and impact within the Greek Chamber of Commerce. Utilizing the Webster and Watson (2002) methodology, the review examines a broad range of literature to design and analyze a DEE framework. The study emphasizes the significance of innovation and digital collaboration in fostering entrepreneurship. The review identifies key themes including technological platforms, e-governance, and user satisfaction. Findings indicate that DEEs play a crucial role in enhancing business development through digital means. The study aims to bridge the knowledge gap in DEE literature and provide a practical foundation for similar initiatives. The research underscores the need for digital transformation in business ecosystems to support extroversion, innovation, and targeted entrepreneurial actions, advocating for cultural, structural, and systemic changes within chambers of commerce to better serve businesses and foster long-term relationships.